‘She felt incredibly ashamed’: gendered (cyber-)bullying and the hypersexualized female body - Mahlknecht, Belinda; Bork-Hüffer, Tabea (Gender, place and culture, 2023)
Cyberbullying has become an ever-pressing topic for young people in a time of ubiquitous media. Some of the existing, mostly quantitative studies reveal that (cyber-)bullying is gendered and that female and genderqueer young people are bullied more often and differently than males. However, there is a lack of qualitative studies that look into the specific reproduction and dynamics of gendered discourses in bullying that stretches across entangled socio-material-technological spaces. Informed by insights from digital geographies, gender(-queer) geographies, and interdisciplinary research on (cyber-)bullying, and taking a feminist perspective, this article investigates gendered discourses in young adults’ narratives about (cyber-)bullying. The analysis is based upon 42 written narratives produced by young adults attending upper secondary schools in Austria describing (cyber-)bullying they were involved in as (co-)perpetrators, targets or bystanders. (Cyber-)bullying reported ranges from early undesired reception of sexual content to hypersexualized harassment (by peers) to sexual grooming (by unknown adults). Rather than focusing on the narrators’ active or passive roles in the bullying practices themselves, through narrative analysis we reveal how, in their accounts of (cyber-)bullying attacks, our participants—often unintentionally—reproduce gender roles and ideals of femininity and masculinity, and therewith deeply ingrained heteronormative discourses that prevail in Austrian society. For female young people, the persistent and complex ‘sexual double standard’ is particularly harmful in serving to legitimize undesired hypersexualization of their bodies online while simultaneously prohibiting their right to self-determined sexual practices online.